2019
DOI: 10.3390/su11246884
|View full text |Cite
|
Sign up to set email alerts
|

Drivers for Sustainable Business Models in Start-Ups: Multiple Case Studies

Abstract: Mechanisms that large organizations employ to facilitate corporate social responsibility (CSR) engagement simply do not apply to start-ups due to distinct differences. The purpose of this study was to gain insight into how start-ups strive for sustainability in their business models by investigating internal and external drivers related to organizational processes, managerial characteristics, and stakeholder expectations. We explored key factors such as decision-making regarding CSR engagement, business values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Last, even though they did not discuss universities, Eulalia and Romuald [33] examined success factors of start-ups in the European Union. Emphasizing that it is imperative for start-up companies to boost innovation levels, the competitiveness of national economies also needs to be considered as a factor impacting sustainability [34], this study determined the key success factors of start-ups in the EU and classified the gap between developed and lagging member states. The results indicated that more developed countries offer an institutional competitive advantage to start-ups through such factors as institutions, human capital, and certain dimensions of social capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Last, even though they did not discuss universities, Eulalia and Romuald [33] examined success factors of start-ups in the European Union. Emphasizing that it is imperative for start-up companies to boost innovation levels, the competitiveness of national economies also needs to be considered as a factor impacting sustainability [34], this study determined the key success factors of start-ups in the EU and classified the gap between developed and lagging member states. The results indicated that more developed countries offer an institutional competitive advantage to start-ups through such factors as institutions, human capital, and certain dimensions of social capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our literature review indicates a need to specify the purpose of the programme [6,11,19]. The programme displays a lack of clarity concerning whether enterprising activity is seen as endogenous or exogenous to existing market forces; whether to seek development or business productivity [6]; whether to build a programme targeting rural or urban contexts [46,48,49]; whether to specify short-term objectives and learning methods [11,26]; whether to seek social and philanthropic utility, innovative development or economic growth and productivity [6,20]; and, last but not least, whether to establish selection parameters which mirror the relevant target groups, their start-up maturity and their context [6,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Sustainability is an area which is particularly poorly defined in our case programme, rather considering a general definition, objectives or an overall purpose of the programme. Poorly definitions of sustainability may lead to difficulties in adopting sustainability practice [20]. This has led to doubts about the real function or inclusion of sustainability as a dimension in the programme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that a networked and collaborative environment (ecosystem) is essential for triggering co-creative paths able to meet start-ups strive for development as well as other actors (stakeholders) expectations now and in the future (Ruokolainen et al, 2011). Thus, start-ups can be considered 'born sustainable' or sustainability-oriented when they act-inspired by entrepreneurs' mind-set and valuestaking into account sustainability and value implications at different ecosystem levels (micro, meso and macro) and for different individuals and/or collective actors (or stakeholders) (Voinea et al, 2019). However, it worth noting that further research is still needed to better understand how start-ups engage and, thus, interact with other ecosystem actors (e.g., PIJ/Volume 4 -Issue 2/2019 ISSN: 2499-1333 incubators, research centres, institutions, clients, etc.…”
Section: 2mentioning
confidence: 99%